WISDOM DICTIONARY IN MODERN EDUCATION - Xolnazarova Dinara,; Poʻlatova Sevinch,; Tolibjonova Munisa, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation This article discusses the role of a “Wisdom Dictionary” in modern education and its impact on students’ intellectual and personal development. A wisdom dictionary is a collection of meaningful words, expressions, and life lessons that help learners expand  their  vocabulary  and  understand  deeper  meanings  of  language.  The  study shows how using such a dictionary can improve critical thinking, moral awareness, and communication skills. It also highlights how students can connect language learning with real-life experiences.